2017
DOI: 10.15171/jcvtr.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic therapy in patients with ST-segment elevation myocardial infarction: Accelerated versus standard Streptokinase infusion regimen

Abstract: Introduction: Timely fibrinolysis for acute ST-segment elevation myocardial infarction (STEMI) reduces infarct size and hence preserves LV function and reduces mortality. Optimal regimen of streptokinase (SK) infusion in such patients is a matter of interest. The current study aimed to compare efficacy and safety of accelerated SK infusion regimen in patients with STEMI versus the standard one. Methods: One hundred consecutive STEMI patients were randomly allocated into one of 2 groups: group I (50 patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Our review found only eight relevant articles investigating the potential mechanisms underlying streptokinase-induced hypotension, despite hypotension being a well-recognised side effect of streptokinase therapy that has been still poorly understood to date [ 12 , 13 ]. A vast majority of the scientific investigation on the pharmacokinetics of streptokinase was based on in vitro and animal studies, which findings may not be directly transferrable to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review found only eight relevant articles investigating the potential mechanisms underlying streptokinase-induced hypotension, despite hypotension being a well-recognised side effect of streptokinase therapy that has been still poorly understood to date [ 12 , 13 ]. A vast majority of the scientific investigation on the pharmacokinetics of streptokinase was based on in vitro and animal studies, which findings may not be directly transferrable to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Streptokinase-induced hypotension is a well-known side effect of intravenous streptokinase therapy in acute myocardial infarction [ 12 ]. Despite its mild and transient course that is typically reversible with Trendelenburg position or fluid challenge, it can produce an undesirable effect by interfering with streptokinase fibrinolytic activity as the decrease in perfusion pressure during the hypotensive episode restricts the circulation of streptokinase in reaching the targeted sites.…”
Section: Discussionmentioning
confidence: 99%
“…Penambahan inhibitor glikoprotein IIb atau IIIa ke terapi fibrinolitik harus dihindari karena risiko perdarahan mayor yang dilaporkan lebih besar dibandinkan manfaat yang didapat. Pada penelitian Bendary et al, 14 dijelaskan bahwa streptokinase diindikasikan terkait faktor ekonomi yakni biaya, hal ini sesuai dengan teori yang dijelaskan sebelumnya dalam pedoman PERKI dan CCS/CAIC bahwa streptokinase diperlihatkan dengan manfaatnya pada GISSI-1 trial dan harganya yang relatif murah. 9,26 Analisis penelitian Roule et al 19 (Tabel 3) menunjukkan bahwa manfaat fibrinolitik yang dilakukan pada pasien yang ditangani lebih awal yakni dua jam pertama setelah onset gejala dikaitkan dengan tingkat kematian awal dan akhir yang serupa dan peningkatan kelangsungan hidup satu tahun dibandingkan dengan penundaan PPCI.…”
Section: Bahasanunclassified
“…15 The other reported ecacy of accelerated SK in patients with STEMI is 62%. 16 The present study is designed to determine the ecacy of accelerated SK in the treatment of newly diagnosed STEMI. Our major concern to conduct this study was that in Peshawar, data regarding the eect of streptokinase in patients with STEMI is lacking especially in the past 5 years.…”
Section: Introductionmentioning
confidence: 99%